An enhanced harmony search (ENHS) algorithm for solving optimization problems - Taj, Talha A.; Khan, Talha A.; Ijaz, Imran (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
Optimization techniques attracts researchers to formulate a problem and determine its optimum solution. This paper presents an Enhanced Harmony Search (ENHS) algorithm for solving optimization problems. The proposed algorithm increases the convergence and is more efficient than the standard harmony search (HS) algorithm. The paper discusses the novel techniques in detail and also provides the strategy for tuning the decisive parameters that effects the efficiency of the ENHS algorithm. The algorithm is tested on various benchmark functions, a real world optimization problem and a constrained objective function. Also, the results of ENHS are compared to standard HS, and various other optimization algorithms. The ENHS algorithms proves to be significantly better and more efficient than other algorithms. The simulation and testing of the algorithms is performed in MATLAB.